2015
DOI: 10.1097/meg.0000000000000115
|View full text |Cite
|
Sign up to set email alerts
|

Entecavir as a first-line treatment for hepatitis B virus reactivation following polychemotherapy for chronic lymphocytic leukemia and invasive ductal carcinoma

Abstract: Allowing a rapid and sustained control of HBV replication, entecavir seems to be a promising drug for first-line prompt treatment of HBV reactivation in patients undergoing chemotherapy for hematological as well as solid organ malignancies, with safe long-term use enabling maintenance of resolved hepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…A previous study revealed that administration of an anti‐HBV drug, lamivudine, to NPC patients receiving chemotherapy, can reduce the incidences of HBV reactivation and chemotherapy‐related hepatitis . Studies on other types of tumors also revealed that antiviral therapy can reduce the incidence of HBV reactivation . Our results showed that the no‐antivirus group had 3 patients with liver injuries higher than grade 1, whereas no patient had liver injuries higher than grade 1 in the antivirus group; however, no statistically significant difference existed between the two groups.…”
Section: Discussioncontrasting
confidence: 40%
“…A previous study revealed that administration of an anti‐HBV drug, lamivudine, to NPC patients receiving chemotherapy, can reduce the incidences of HBV reactivation and chemotherapy‐related hepatitis . Studies on other types of tumors also revealed that antiviral therapy can reduce the incidence of HBV reactivation . Our results showed that the no‐antivirus group had 3 patients with liver injuries higher than grade 1, whereas no patient had liver injuries higher than grade 1 in the antivirus group; however, no statistically significant difference existed between the two groups.…”
Section: Discussioncontrasting
confidence: 40%
“…Only a retrospective study [40] and two case series [41,42] described successful treatment with drugs with higher antiviral potency and high genetic barrier, such as entecavir or tenofovir, in haematologic patients.…”
Section: Hbv-negative Allo-hsct Recipient With An Anti-hbv-positive Dmentioning
confidence: 99%
“…Numerous case reports and series describe death due to liver failure despite the introduction of lamivudine at the onset of HBV reactivation [ 124 - 128 ]. Only a few cases of successful treatment of HBV reactivation with entecavir or tenofovir have been published [ 42 , 129 - 131 ]. Despite the paucity of data regarding the efficacy of entecavir and tenofovir to treat established HBV reactivation, the ability of these drugs to rapidly reduce HBV DNA make them attractive alternatives to lamivudine in patients who experience HBV reactivation to potentially abrogate the risk of liver failure and mortality.…”
Section: How Do We Manage Hepatitis B Reactivation?mentioning
confidence: 99%